Exploring the Impact of Language Models on Undergraduate Thesis Writing Skills among Higher Education Students - Ilma, Agnia; Riza Ady Sampurna (Pustaka Peradaban, 2024)
This article explores the impact of language models on undergraduate thesis writing skills among higher education students. With advancements in technology, language models have become integral to the digital writing landscape. This study examined the influence of language models on students' confidence and motivation in academic writing. The research employs a qualitative approach, conducting semi-structured interviews with five students from an English Language Education program who utilized AI tools in their thesis writing process. Despite acknowledging the advantages, participants underscored challenges encompassing overreliance, inaccuracies, and disruptions in the natural flow of their writing. The impact of these tools on participants' confidence and motivation in academic writing manifested diversely, introducing varying degrees of perceived artificiality in writing proficiency. There were already numerous researches regarding the pretinence of language models usage on students’ writing aptitude. However, there remains a gap in understanding their specific influence on undergraduate thesis writing. Thematic analysis of the interview data reveals insights into the influence of language models, on the writing proficiency of higher education students engaged in the process of crafting undergraduate theses. Employing a methodology encompassing interviews, participants reported noteworthy enhancements in the coherence, clarity, grammar, syntax, and vocabulary of their theses facilitated by the utilization of these language tools. Overall, the incorporation of language models in the writing process emerged as a catalyst for heightened efficiency, skills development, and enhanced clarity in undergraduate theses, affirming the constructive role of AI technology in educational settings. Individualized experiences with language models exhibited variance contingent upon personal preferences and attitudes towards the writing process.